Comparison of economic activity leading U.S. sports leagues - Strikalenko, E. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The main activities of the leading sports leagues were described. Sources of revenue and expenditure were identified. The economic performance of professional sports leagues of the United States of America was compared. In the course of the study of economic efficiency of the leading American sports leagues are defined payroll (expense commands on the salaries of players for each team, the total payroll in the League and the average payroll, respectively, for each of the American League. The largest estimates on wages, both in the League and in teams - in the National football League, the largest player's contract - in the Highest League baseball, the minimum wage in the National hockey League; the highest average wages, a greater percentage of athletes with a salary of more than 1 million. $ (82,85 %) in the National basketball Association were showed. This difference in the maximum income of the League and of average wages is due to several factors: the number of players in the team, the number of games in a season, and expenses on carrying out of competition and training activities.